On the propagation and interaction of the low-frequency ion-acoustic multi-solitons in a magnetoplasma having nonextensive electrons using Hirota bilinear method - Aljawhara H Almuqrin; Delmas V Douanla; Camus GL Tiofack; Alim; Alidou Mohamadou; Sherif ME Ismaeel; Samir A El-Tantawy (Journal of Low Frequency Noise, Vibration and Active Control)
This work explores the low-frequency ion-acoustic waves (IAWs) formation and interaction in a magnetized plasma containing dynamical inertial positive ions and inertialess hot and cold electrons that obey the q -nonextensive statistics. The reductive perturbation method is utilized to obtain the Korteweg-de Vries (KdV) equation for describing the low-frequency IAWs in proximity to critical values of the pertinent physical variables in the system. At specific essential plasma compositions, the modified KdV (mKdV) equation is derived for the parameter values at which the KdV model fails to analyze the nonlinear dynamics of the low-frequency IAWs adequately. The current plasma model accommodates both positive polarity (compressive) and negative polarity (rarefactive) solitons. The Hirota bilinear method generates multi-soliton solutions for the mKdV equation. We calculate the first three solitons in the series to understand the propagation dynamics of the multi-solitons and analyze them graphically to comprehend the propagation mechanism of these waves inside the present plasma model. The impact of the plasma parameters on the properties of multi-soliton solutions is discussed. Furthermore, the novelty of the results present in our study concerns the more complex scenario of interaction of three-solitons of opposite polarities, namely, two compressive solitons and a rarefactive soliton. One of the main characteristics observed during interactions between compressive and rarefactive solitons is the appearance of two humps or two dips at the moment of collision. The importance of this study lies in the fact that nonlinear wave propagation in plasmas is an emerging area of research that provides an understanding of energy or particle transport phenomena in laboratory and astrophysical plasmas.